Pengembangan Media Buku Bergambar CATEBA Untuk Melatih Kemampuan Keaksaraan Anak Kelompok B - Rabiatul Adwiyah; Gunawan Gunawan; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Publication Center, 2022)
This study aims to produce an appropriate CATEBA picture book media, so that it can be used in learning activities to train the literacy skills of group B children. This study uses the Research and Development (R&D) method with the ADDIE model or Analysis, Design, Development, Implementation, and Evaluation. The product developed is CATEBA picture book media (Find, Paste, Read) with play activities to find letters, paste letters, and read which have been assessed and validated by media validators, material validators, and school teachers. The data collection technique used observation, documentation, and validation sheet questionnaires. The research instrument was in the form of a validation questionnaire by experts. The data obtained were analyzed using a qualitative descriptive method. The results showed that the CATEBA picture book produced based on the results of the expert's assessment obtained the